Food and country [videorecording (DVD)] - Reichl, Ruth; Achatz, Grant; Waters, Alice (Greenwich Entertainment, 2024)
Trailblazing food writer and best-selling memoirist Ruth Reichl examines the precarious state of America's food system. Reaching through political and social divides, she meets with small farmers, ranchers, and chefs risking it all to survive. Through Reichl's eyes, we see humanity and struggle behind the food we eat.